2023
DOI: 10.1186/s12875-022-01957-8
|View full text |Cite
|
Sign up to set email alerts
|

Between empathy and anger: healthcare workers’ perspectives on patient disengagement from antiretroviral treatment in Khayelitsha, South Africa - a qualitative study

Abstract: Background & objectives The benefits of long-term adherence to antiretroviral therapy (ART) are countered by interruptions in care or disengagement from care. Healthcare workers (HCWs) play an important role in patient engagement and negative or authoritarian attitudes can drive patients to disengage. However, little is known about HCWs’ perspectives on disengagement. We explored HCWs’ perspectives on ART disengagement in Khayelitsha, a peri-urban area in South Africa with a high HIV burden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Addressing attitudes and behaviors may require more in-depth work and empathy training; incorporating these principles into medical curricula could be a valuable step forward 43 . A study exploring HCW attitudes among this population before the intervention showed HCWs had contradictory feelings of empathy and anger towards disengagement: HCWs felt frustrated about disorganized systems and high patient demand, which could be misdirected toward re-engaging patients, who may have more demanding clinical and psychosocial needs 15 . Despite system pressures potentially influencing full adoption of welcoming attitudes, specific elements of the program (perceived decreased waiting times, increased same-day ART, appreciation of counselling) were positively noted by HCWs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Addressing attitudes and behaviors may require more in-depth work and empathy training; incorporating these principles into medical curricula could be a valuable step forward 43 . A study exploring HCW attitudes among this population before the intervention showed HCWs had contradictory feelings of empathy and anger towards disengagement: HCWs felt frustrated about disorganized systems and high patient demand, which could be misdirected toward re-engaging patients, who may have more demanding clinical and psychosocial needs 15 . Despite system pressures potentially influencing full adoption of welcoming attitudes, specific elements of the program (perceived decreased waiting times, increased same-day ART, appreciation of counselling) were positively noted by HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…During HCW interviews we explored their knowledge and understanding of the intervention principles, including their understanding and value of the various elements implemented, with a strong focus on exploring attitudes and behaviors toward patient disengagement from care, thereby aiming to evaluate the specific teachings in the person-centered care training. Design of topic guides was influenced by an evaluation of HCWs’ perceptions of disengagement amongst the same population conducted before the intervention 15 . Topic guides were pretested, using separate guides for HCWs and patients, and revisions were made after debriefing from pilot interviews.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinic appointment attendance has emerged as a strong predictor for longer term retention of ART clients since missed appointments can lead to a reluctance to return to care and ultimately result in disengagement from HIV treatment (79). Beyond the risk of disengagement from ART, when care recipients are late for, or miss their scheduled appointments, this may place additional pressure on already constrained clinic staff to trace and bring clients back to care, negatively affecting the quality-of-service delivery (911).…”
Section: Introductionmentioning
confidence: 99%